Morphological Effects of Combined Systemic Administration of Fluoxetine and Sildenafil in the Murine Hippocampus - Mahmoodi, M.; Shahidi, S.; Hashemi-Firouzi, N.; Komaki, A. (Нейрофизиология, 2013)
We examined the effects of fluoxetine, a selective serotonin re-uptake inhibitor, of sildenafil,
a phosphodiesterase-5 (PDE5) inhibitor, and of combined administration of these agents
on morphometric characteristics of principal cells of the murine hippocampus. Fluoxetine
(5 mg/kg), sildenafil (2 mg/kg), or a combination of these drugs in the above doses were
administered i.p. daily for 2 weeks to male mice. Hippocampal sections (5 mm thick) were
stained with hematoxylin/eosin. Both drugs and their combination evoked no considerable
changes in the dimensions of pyramidal cells in the CA1 and CA2 areas and in the dentate
gyrus (DG), except for a trend toward some decrease of this parameter after fluoxetine
injections in the CA1 area. Combined administration of fluoxetine and sildenafil provided
significant decreases in the density of pyramidal neurons (their mean number per 10 mm of
the slice) in the CA1 area and DG. Isolated administration of fluoxetine resulted in significant
but less intense decreases in the density of principal cells in the CA2 area and DG. Possible
mechanisms of the effects of the mentioned drugs are discussed. Further studies of interaction
between fluoxetine and sildenafil in their effects on morphological and physiological
properties of cells in different subregions of the hippocampus are recommended. Ми досліджували вплив флуоксетину (селективного інгібітора зворотного захвату серотоніну), силденафілу (інгібітора фосфодіестерази-5, PDE5) та їх сукупного введення
на морфометричні характеристики основних (пірамідних)
клітин гіпокампа мишей. Флуоксетин (5 мг/кг), силденафіл
(2 мг/кг) або комбінація цих агентів у зазначених дозах уводилися самцям мишей внутрішньоочеревинно щоденно протягом двох тижнів. Зрізи гіпокампа завтовшки 5 мкм забарвлювали гематоксиліном та еозином. Обидві речовини та їх
комбінація не викликали значних змін розмірів пірамідний
нейронів у зонах CA1, CA2 та зубчастої звивини (ЗЗ), певна тенденція до зменшення зазначеного параметра спостерігалася після ін’єкцій флуоксетину в зоні CA1. Сукупна дія
флуоксетину та силденафілу призводила до істотного зменшення щільності пірамідних нейронів (їх середньої кількості з розрахунку на 10 мкм зрізу) у зоні CA1 та ЗЗ. Обговорюються можливі механізми ефектів згаданих агентів.
Доцільними є подальші дослідження особливостей взаємодії флуоксетину та силденафілу на морфологічні та фізіологічні характеристики клітин у різних підрозділах гіпокампа.